P-TEFb goes viral - Zaborowska, Justyna; Isa, Nur Firdaus; Murphy, Shona (John Wiley and Sons Inc., 2016)
Positive transcription elongation factor b (P-TEFb), which comprises cyclin-dependent kinase 9 (CDK9) kinase and cyclin T subunits, is an essential kinase complex in human cells. Phosphorylation of the negative elongation factors by P-TEFb is required for productive elongation of transcription of protein-coding genes by RNA polymerase II (pol II). In addition, P-TEFbmediated phosphorylation of the carboxyl-terminal domain (CTD) of the largest subunit of pol II mediates the recruitment of transcription and RNA processing factors during the transcription cycle. CDK9 also phosphorylates p53, a tumor suppressor that plays a central role in cellular responses to a range of stress factors. Many viral factors affect transcription by recruiting or modulating the activity of CDK9. In this review, we will focus on how the function of CDK9 is regulated by viral gene products. The central role of CDK9 in viral life cycles suggests that drugs targeting the interaction between viral products and P-TEFb could be effective anti-viral agents.